The Effect of Operating Cash Flow and Net Profit on Stock Return - Susetyo, Dwinanto Priyo Susetyo; Sarah, Siti Sarah (Jurnal Akuntansi dan Sistem Informasi, 2026)
The purpose of this study is to explore the effect of operating cash flow (OCF) and net profit (NP) on stock returns (SR). The research design uses a quantitative approach. The secondary data source, using a ratio scale, is financial statement data for 32 quarters from 2015 to 2022, selected using a purposive sampling technique. The data analysis method, adapting a multiple linear regression model, was estimated using SPSS v.27, with significance testing using the t-statistic and F-statistic criteria at a threshold of 1,96, at an alpha 0,05. The results confirm that OCF has a positive and significant effect on SR, but NP does not. Interestingly, exploratory results show evidence that OCF and NP simultaneously have a positive and significant effect on SR. OCF and NP together can explain variance in SR, with relatively low predictive power. The implication is that the level of smoothness and balance of cash flow from operating activities is one of the important factors for measuring management performance in ensuring the smooth operation of the company, and enabling the achievement of levels of revenue, profit, return on investment, and various liabilities in a given accounting period.